To realize a variety of structural color adjustments via lossy-dielectric-based Fabry-Perot cavity structure - Rahman, Md Abdur; Kim, Dong Kyu; Lee, Jong-Kwon; Byun, Ji Young (WALTER DE GRUYTER GMBH, 2022)
Structural colors with tunable properties have extensive applications in surface decoration, arts, absorbers, and optical filters. Planar structures have more advantages over other forms studied to date due to their easy manufacturability. Metal-insulator-metal-based structures are one of the known methods to fabricate structural colors where colors can be tuned mainly by the thickness of the intermediate lossless insulator layer. However, generating colors by MIM structure requires a thin metallic layer on top, and the top metals' abrasiveness and/or oxidation may degrade the colors quickly. Thus, we propose a lossy dielectric layer to replace the top metallic layer as a solution to ensure the structure's durability by preventing scratches and oxidation. Herein, CrON/Si3N4/Metal structures have been studied where theoretical investigations suggest that highly saturated colors can be generated in the lossy-lossless dielectric structures. Experimental data validated such simulations by revealing a range of vivid colors. Furthermore, these structures can easily achieve strong light absorption (SLA) even for a thick top layer of similar to 100 nm. The colors realized by these structures are appeared due to a combination of the interference effect of the asymmetric Fabry-Perot cavity structure and the absorption rate in the CrO x N1-x layer.